Visual Deficiency in Wallenberg"s Syndrome Wallenbergov sindrom i poremećaj vida - Bjeloš, Mirjana; Križanović, Ana; Bušić, Mladen; Kuzmanović Elabjer, Biljana (2021)
The aim of this case report of a 47-year-old woman who suffered from acute right-sided medullar ischemic stroke was to define the range of visual impairment in Wallenberg"s syndrome (WS). The patient complained of unbearable environmental tilt and rotating visual perception. On examination, 11 months following the stroke, the patient manifested rightsided postural inclination and gaze ipsipulsion. The fixation in primary position was unstable, after a conjugate ipsipulsion ensued, spontaneous corrective saccades and a horizontal-rotational jerking nystagmus beating away from the side of the lesion were generated. Monocular visual acuity (right eye: 0.4 logMAR distance and 0.2 logMAR near; left eye: 0.1 logMAR distance and 0.0 logMAR near) was significantly better than binocular (0.63 logMAR distance and near). Fluent reading was impossible. Contralateral smooth pursuits were more impaired. Saccades were defective manifesting right hypermetria and left hypometria. Visual field was constricted to central 10 – 20°. A diagnosis of Wallenberg"s syndrome was made. Occlusion was prescribed. Review of literature demonstrated lack of evidence-based guidelines for ophthalmic assessment and treatment of visual impairment in WS. Oculomotor abnormalities, oscillopsia and tilt illusion cause significant impact to daily life. Early post-stroke ophthalmological evaluation is thus mandatory in order to offer timing treatment.
Cilj je ovoga prikaza slučaja 47-godišnje bolesnice s desnostranim medularnim ishemijskim moždanim udarom definirati opseg oštećenja vida kod Wallenbergova sindroma (WS). Bolesnica se žalila na nesnosan osjećaj nagiba okoline i rotirajuću vizualnu percepciju. Na kliničkome pregledu jedanaest mjeseci nakon moždanoga udara manifestirala je desnostranu inklinaciju trupa i ipsipulziju pogleda. U primarnom položaju fiksacija je bila nestabilna, a slijedila ju je konjugirana ipsipulzija te spontane korekcijske sakade i horizontalno-rotacijski trzajući nistagmus usmjeren suprotno od strane lezije. Monokularna vidna oštrina (desno oko: 0.4 logMAR daljina i 0.2 logMAR blizina; lijevo oko: 0.1 logMAR daljina i 0.0 logMAR blizina) bila je značajno bolja od binokularne (0,63 logMAR daljina i blizina). Fluentno čitanje nije bilo moguće. Pokreti glatkoga praćenja u smjeru suprotnom od lezije bili su otežani. Sakade su manifestirale desnostranu hipermetriju i lijevostranu hipometriju. Vidno polje bilo je suženo na središnjih 10 – 20 °. Postavljena je dijagnoza Wallenbergova sindroma. Propisana je okluzija. Pregled literature pokazao je nedostatak smjernica medicine utemeljene na dokazima za oftalmološku procjenu i liječenje oštećenja vida kod WS-a. Okulomotorne abnormalnosti, oscilopsija i iluzija nagiba značajno utječu na svakodnevni život. Zaključno, nakon moždanog udara nužna je rana oftalmološka procjena kako bi se s liječenjem započelo na vrijeme.
Bibliografija
Summary.